Real property : ownership and registration - Mamalateo, Victorino C.; Mamalateo-Jusay, Mary Joy B. (Manila, Philippines : Rex Book Store, 2021)
This book is written exactly to address the common complaints and the legal problems of property owners and potential property owners or buyers.
CHAPTER 1. Development of the Regalian Doctrine -- 2. Classification of Property -- 3. Ownership and Co-ownership of Property -- 4. Modes of acquiring property ownership -- 5. Agrarian Reform -- 6. Urban Land Reform and housing -- 7.Introduction to Land Registration -- 8. Ordinary Registration Proceedings -- 9. Recording of instruments involving unregistered Lands and subsequent registration of registered lands -- 10. Cadastral registration proceedings and action for reversion of title to government -- 11. Reconstitution of title -- Chapter 12. Assurance Fund.
Keywords: REAL PROPERTY -- PHILIPPINES